Weight management practices of 2012 Olympians in combat sports - Jones, L. K.; Meyer, N. L.; Gibson, J. C. (International Journal of Wrestling Science, 2014)
To understand the reported weight management practices of 2012 Olympians in combat sports. Methods: A 17-question electronic survey was distributed to139 English-speaking Olympians in judo, wrestling, taekwondo, and boxing via National Governing Bodies. Data were analyzed using descriptive and frequency statistics. Percent weight loss was compared by sport, gender, and placing using a general linear mixed ANOVA. Results: Thirty responses were collected (15 males, 15 females; age = 26.7+/- 4.7yr, 8 medalist, 22 non-medalists). When heavy weights are excluded, athletes mostly reported following low calorie diets (46%) and exercising more (58%) to manage weight. No athlete reported using weight loss supplements, pills, vomiting, or laxatives. Prior to the Olympic games, mean weight loss was 5.2+/-3.0kg at 4 weeks, 3.9+/-2.4kg at 2 weeks and 2.3+/-1.7kg 1-2 days prior, with a significant time effect at p<0.001. When placing was compared, medalists reported less weight loss than non-medalists at all time points, although this was not statistically significant. Conclusion: This study shows that Olympic athletes practiced weight control methods less destructive than previously reported in the literature in developmental groups. Integrating these results into educational approaches may help to shift the current weight management practices in these sports.